Derechos Humanos: realidad migratoria de la movilidad humana de ciudadanos venezolanos en Esmeraldas – Ecuador. Periodo 2023-2024 - Quintero Torres, Gioconda Paquita (2025)
The objective of this study was to analyze the human rights situation of Venezuelan migrants who transit or arrive in the Esmeraldas-Ecuador canton to identify challenges and obstacles in compliance with established legal norms. The study was developed using descriptive and documentary methodology, which allowed understanding the violation of human rights of Venezuelan migrants living in Esmeraldas; it was also necessary to apply qualitative and quantitative approaches to collect information and statistical results. The sample consisted of 80 randomly selected Venezuelans residing in the Esmeraldas canton, and 3 key informants who were authorities from different government institutions in the same canton, to whom a questionnaire and an interview guide were applied respectively. The results showed that state and non-governmental efforts aimed at ensuring the social and economic inclusion of this population are insufficient considering the magnitude of the Venezuelan migration crisis. It was concluded that the migratory reality of human mobility of Venezuelan citizens in Esmeraldas is centered on job insecurity, limited access to basic services, discrimination, regularization and the lack of inclusive policies that promote their economic and social integration.